Comparative study on the growth performance of Spirulina platensis on modifying culture media - Soni, Ruma Arora; Sudhakar, K.; Rana, R. S. (Elsevier Ltd, 2019)
India faces a severe challenge to ensure adequate nutrition for children and women. Chronic child nutrition deficiency is more prevalent in Madhya Pradesh state of India. Spirulina, multicellular and filamentous cyanobacterium are considered an absolute food supplement to combat malnutrition in Asian and African countries. Spirulina cultivation requires sufficient aeration, agitation and proper light intensity for enhanced biomass yield, cell productivity, specific growth rate, and protein content. This paper presents a novel experimental approach to maximize biomass yield, minimize evaporation rate and respiration losses in a laboratory scale closed reactor and open pond system. Lab scale open pond and closed reactor system were designed for spirulina cultivation under dry climatic conditions at Bhopal, India. Zarrouk media was used as standard and modified organic media was prepared by changing the nitrogen source. Temperature and other input parameters were maintained. Aeration was done manually in an open pond, and the air pump was used in the case of a closed reactor system. Biomass yield obtained from an open pond system was 11.34 g/l, and 12.28 g/l in the closed reactor system. Doubling time was also less in the closed reactor in comparison with the open pond system. Urea seems to be a promising alternative source of low-cost nitrogen for Spirulina cultures. From the experimental results, it is concluded that modified organic media and closed reactor system could be used for better biomass yield.